A recurrent de novo missense mutation in UBTF causes developmental neuroregression. (2nd January 2018) - Toro, Camilo; Hori, Roderick T; Malicdan, May Christine V; Tifft, Cynthia J; Goldstein, Amy; Gahl, William A; Adams, David R; Harper, Fauni; Wolfe, Lynne A; Xiao, Jianfeng; Khan, Mohammad M; Tian, Jun; et al.
Abstract: UBTF (upstream binding transcription factor) exists as two isoforms; UBTF1 regulates rRNA transcription by RNA polymerase 1, whereas UBTF2 regulates mRNA transcription by RNA polymerase 2. Herein, we describe 4 patients with very similar patterns of neuroregression due to recurrent de novo mutations in UBTF (GRCh37/hg19, NC_000017.10: g.42290219C > T, NM_014233.3: c.628G > A) resulting in the same amino acid change in both UBTF1 and UBTF2 (p.Glu210Lys [p.E210K]). Disease onset in our cohort was at 2.5 to 3 years and characterized by slow progression of global motor, cognitive and behavioral dysfunction. Notable early features included hypotonia with a floppy gait, high-pitched dysarthria and hyperactivity. Later features included aphasia, dystonia, and spasticity. Speech and ambulatory ability were lost by the early teens. Magnetic resonance imaging showed progressive generalized cerebral atrophy (supratentorial > infratentorial) with involvement of both gray and white matter. Patient fibroblasts showed normal levels of UBTF transcripts, increased expression of pre-rRNA and 18S rRNA, nucleolar abnormalities, markedly increased numbers of DNA breaks, defective cell-cycle progression, and apoptosis. Expression of mutant human UBTF1 in Drosophila neurons was lethal. Although no loss-of-function variants are reported in the Exome Aggregation Consortium (ExAC) database and Ubtf −/− is early embryonic lethal in mice, Ubtf +/− mice displayed only mild motor and behavioral dysfunction in adulthood. Our data underscore the importance of including UBTF E210K in the differential diagnosis of neuroregression and suggest that mainly gain-of-function mechanisms contribute to the pathogenesis of the UBTF E210K neuroregression syndrome.